Survival and quality of life after early discharge in low-risk pulmonary embolism. Issue 2 (4th February 2021) - Barco, Stefano; Schmidtmann, Irene; Ageno, Walter; Anušić, Toni; Bauersachs, Rupert M.; Becattini, Cecilia; Bernardi, Enrico; Beyer-Westendorf, Jan; Bonacchini, Luca; Brachmann, Johannes; Christ, Michael; Czihal, Michael; et al.
Introduction: Early discharge of patients with acute low-risk pulmonary embolism requires validation by prospective trials with clinical and quality-of-life outcomes. Methods: The multinational Home Treatment of Patients with Low-Risk Pulmonary Embolism with the Oral Factor Xa Inhibitor Rivaroxaban (HoT-PE) single-arm management trial investigated early discharge followed by ambulatory treatment with rivaroxaban. The study was stopped for efficacy after the positive results of the predefined interim analysis at 50% of the planned population. The present analysis includes the entire trial population (576 patients). In addition to 3-month recurrence (primary outcome) and 1-year overall mortality, we analysed self-reported disease-specific (Pulmonary Embolism Quality of Life (PEmb-QoL) questionnaire) and generic (five-level five-dimension EuroQoL (EQ-5D-5L) scale) quality of life as well as treatment satisfaction (Anti-Clot Treatment Scale (ACTS)) after pulmonary embolism. Results: The primary efficacy outcome occurred in three (0.5%, one-sided upper 95% CI 1.3%) patients. The 1-year mortality was 2.4%. The mean±sd PEmb-QoL decreased from 28.9±20.6% at 3 weeks to 19.9±15.4% at 3 months, a mean change (improvement) of −9.1% (p<0.0001). Improvement was consistent across all PEmb-QoL dimensions. The EQ-5D-5L was 0.89±0.12 at 3 weeks after enrolment and improved to 0.91±0.12 at 3 months (p<0.0001). Female sex and cardiopulmonary disease were associated with poorer disease-specific and generic quality of life; older age was associated with faster worsening of generic quality of life. The ACTS burden score improved from 40.5±6.6 points at 3 weeks to 42.5±5.9 points at 3 months (p<0.0001). Conclusions: Our results further support early discharge and ambulatory oral anticoagulation for selected patients with low-risk pulmonary embolism. Targeted strategies may be necessary to further improve quality of life in specific patient subgroups. The results of the complete primary outcome analysis of the HoT-PE study, as well as long-term mortality and quality-of-life data, support early discharge and ambulatory oral anticoagulation with rivaroxaban for selected patients with acute low-risk PE https://bit.ly/32qX0mu